SUMBER PENDAPATAN RUMAH TANGGA PETANI SELAMA MASA PEREMAJAAN KELAPA SAWIT DI DESA ANIK DINGIR KECAMATAN MENYUKE KABUPATEN LANDAK - Popilianus, Hendra; Marisi Aritonang; Wanti Fitrianti (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Rejuvenation (replanting) of oil palm is the process of replanting plants that are similar to the previous plant. This planting was carried out on the grounds that the old plants were too tall and therefore difficult to harvest, the plants were old, and the plant productivity was low. This research aims to analyze farmers' sources of income during the oil palm replanting period. The data sources used in this research are primary and secondary data. The data analysis method used is quantitative descriptive analysis. Quantitative descriptive analysis was used to determine the amount of household income of farmers who were carrying out replanting in Anik Dingir Village, Menyuke District, Landak Regency. The work most farmers do during rejuvenation of on-farm sectors is oil palm farming apart from replanting, from the non-farm sector as traders, while those from the off-farm sector work as rice workers. The most profitable income for farmers is in the on-farm sector with an average amount of IDR 7,835,000/month. The total income of those who work as farmers is IDR 100,924,000/month with an average amount of IDR 6,728,000/month. Meanwhile, the total income of non-farmers is greater, reaching IDR 245,953,000 with an average of IDR 15,372,000/month. According to the results of the data in this research, the sector that plays a major role in household income is the on-farm sector. Farming businesses that play a big role in the on-farm sector are oil palm farming apart from replanting, in the non-farm sector traders, while in the off-farm sector are workers in harvesting or palm fertilizer. The level of farmer welfare is in the high category, namely 68%, amounting to 21 people, in the medium category, namely 32%, amounting to 10 people. So it can be said that people who take part in oil palm rejuvenation (replanting) in Anik Dingir Village, Menyuke District, Landak Regency are people who have a high level of welfare or are categorized as very capable, although there are some who are in the medium category. In this way, the oil palm rejuvenation or replanting process will not reduce farmers' welfare because all costs of the replanting process are borne by the government.